Naturally Acquired Binding-Inhibitory Antibodies to Plasmodium vivax Duffy Binding Protein and Clinical Immunity to Malaria in Rural Amazonians. (30th August 2016) - Nicolete, Vanessa C.; Frischmann, Sarah; Barbosa, Susana; King, Christopher L.; Ferreira, Marcelo U.
Abstract : Background: Antibodies to the cysteine-rich domain II of Plasmodium vivax Duffy binding protein (PvDBP) can inhibit binding of this parasite ligand to its receptor on red blood cells, the Duffy antigen/receptor for chemokines. These binding-inhibitory antibodies (BIAbs) also inhibit P. vivax invasion of reticulocytes in vitro. Methods: To investigate whether naturally acquired anti-PvDBP antibodies are associated with reduced risk of clinical malaria in a population exposed to low levels of P. vivax transmission, we measured total levels of immunoglobulin G antibodies to 5 PvDBP variants and used a functional in vitro assay to quantify their binding-inhibitory activity in a cohort of 466 rural Amazonians followed up for up to 37 months. Results: No association between total immunoglobulin G antibody responses to any PvDBP variant and risk of symptomatic, laboratory-confirmed vivax malaria was observed in this cohort. However, a Cox proportional hazards model, adjusted for age, sex, and genotype for the Duffy antigen/receptor for chemokines, showed a >40% decrease in the prospective risk of clinical vivax malaria in subjects with the strongest BIAb responses (upper and middle terciles). High BIAb responses were mostly PvDBP variant transcending and stable over time. Conclusions: Strong naturally acquired BIAb responses are associated with a reduced risk of clinical P. vivax malaria in rural Amazonians.